Distribution of cesium-137 in reindeer - Rissanen, Kristina; Rahola, Tua; Aro, Pauli (Rangifer, 1990)
The influence of the Chernobyl accident in 1986 on the Finnish reindeer herding area was much smaller than the effects of the nuclear bomb tests in the 1960s. Only in one small area somewhat more Cs-137 was deposited than in the rest of the reindeer herding area. From that area 20 reindeer were chosen for investigation of the distribution of Cs-137. All tissues, organs, the skeleton, digestive tract, hide, head and hooves were sampled quantitatively. Three reindeer were pregnant and also the foetuses were studied. The Cs-137 amounts were determined by gammaspectrometric measurements. The results showed that the differences in the Cs-137 concentrations between muscle tissue from different parts of an individual reindeer were not more than 10 percent. Thus it is not essential from which part of the reindeer meat samples for surveillance purposes are taken. The concentration of Cs-137 in edible tissues other than muscle was lower except in the kidneys and scapula cartilage.